Sustainability and Experiential Marketing Synergy: The Mediating Role of Customer Satisfaction in Building Customer Loyalty - Firda Ainu Sifa; Sri Widyastuti (Greenation International Journal of Economics and Accounting, 2025)
The expansion of Indonesia’s coffee shop sector illustrates a notable transformation in consumer behavior, where purchasing motives are increasingly shaped by experiential value and environmental awareness rather than solely by product quality. Kopi Nako in Jakarta exemplifies this phenomenon through the implementation of the Daur Baur sustainability concept and an aesthetic store atmosphere that strengthens customers’ emotional engagement with the brand. This research investigates how Green Marketing and Store Atmosphere influence Customer Loyalty, with Customer Satisfaction serving as a mediating construct. Using an explanatory quantitative approach, data were collected from 304 Kopi Nako customers in Jakarta through an online questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings indicate that both Green Marketing and Store Atmosphere significantly and positively affect Customer Satisfaction and Customer Loyalty. Moreover, Customer Satisfaction significantly mediates the relationships between Green Marketing, Store Atmosphere, and Customer Loyalty. These results highlight that sustainability initiatives and immersive store experiences serve as key drivers of emotional and behavioral loyalty in the modern coffee shop industry.